Salivary neoplasia in dogs and cats: 1996–2017. Issue 3 (17th December 2019) - Cray, Megan; Selmic, Laura E.; Ruple, Audrey
Abstract: Objective: The objectives of this study were to report the contemporary demographical information, provide the incidence of and to assess sex and breed predisposition of salivary gland neoplasia in dogs and cats. Materials and Methods: Information was collected from cats or dogs with salivary neoplasia (cases) and controls from the 26 university veterinary teaching hospitals within the Veterinary Medical Data Base. A total of 56 dogs and 24 cats were identified as having been diagnosed with salivary neoplasia. Results: The incidence of salivary neoplasia in this population was calculated to be 15.3 per 100, 000 dogs and 26.3 per 100, 000 cats. The specific anatomic location of the salivary neoplasia was unable to be determined in 90.8% of cases in both dogs and cats. Results of the univariable conditional logistic regression models revealed no increased risk of salivary neoplasia in dogs or cats of any sex or neuter status (dogs: p = .26; cats: p = .45). There was no breed disposition within the feline species for salivary neoplasia. However, in the conditional logistic regression for dogs, poodles (toy and standard) trended towards significance ( p = .075) with an odds ratio of 6.83 (95% CI: 1.16–40.10) compared to mixed breeds. Conclusions and clinical relevance: The present study's results differ from previous conclusions made in regards to predisposed breeds and tumour location. Additional epidemiological studies should be performed to help in determining risk factors for salivary gland neoplasia. Abstract : The incidence of salivary neoplasia in this population was calculated to be 15.3 per 100, 000 dogs and 26.3 per 100, 000 cats. Sex and neuter status did not increase risk of salivary neoplasia. There was no breed disposition within the feline species but in dogs, poodles (toy and standard) trended towards increased risk of salivary neoplasia compared to mixed breeds.